2015
DOI: 10.1080/01694243.2015.1076592
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of serratiopeptidase transdermal patch by lipid-based transfersomes

Abstract: Serratiopeptidase is a proteolytic enzyme obtained from serratia marcescens strain E-15 and used as anti-inflammatory and analgesic drug. Serratiopeptidase undergoes first pass metabolism, causes the gastrointestinal disturbance and systemic toxicity after oral administration. To overcome the limitations of serratiopeptidase, transdermal drug delivery system is an alternative method. So, the aim of present work was to modulate serratiopeptidase transdermal patch by lipid-based transfersomes. Particle size of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Several studies have reported that deformable liposomes were able to improve in vitro skin delivery of various drugs and to penetrate intact skin in vivo, transferring the therapeutical number of drugs with efficiency compared to subcutaneous administration [15].…”
Section: Transferosomesmentioning
confidence: 99%
“…Several studies have reported that deformable liposomes were able to improve in vitro skin delivery of various drugs and to penetrate intact skin in vivo, transferring the therapeutical number of drugs with efficiency compared to subcutaneous administration [15].…”
Section: Transferosomesmentioning
confidence: 99%
“…The commonly used chemical penetration enhancers and their characteristics are explained in Figure 7. Recently researchers have developed a transdermal patch consisting of lipid-based transferosomes for painless delivery of drug [49].…”
Section: Chemical Penetration Techniquesmentioning
confidence: 99%
“…The paw volume up to tibiotarsal articulation was measured at 0 h (V 0 ), 1, 3, 5 and 24 h (V T ) after carrageenan injection using a plethysmometer. Differences in paw volume between V 0 and V T were taken as a measure of edema [15,16].…”
Section: % Drug Entrapment Efficiency = (Initial Weight -Final Weightmentioning
confidence: 99%
“…Analgesic study: The analgesic activity of the formulation F5 was evaluated by hot-plate technique [16]. Wistar rats weighing between 120-150 g were used for determination of analgesic activity.…”
Section: % Drug Entrapment Efficiency = (Initial Weight -Final Weightmentioning
confidence: 99%